Perdata Putusan Hakim Sebagai Instrumen Perlindungan Hukum Dalam Sengketa Perdata.: Putusan Gugatan Gugur dan Implikasinya dalam Perlindungan Hukum - Hapsari, Kusuma; Prastika, Ileven Junita; Fatimah, Aida; Siswajanthy, Farahdinny; D.Butar Butar, Dinalara (Jurnal Sains Indonesia, 2025)
This research analyses the contribution of judicial decisions as a legal protection tool in the civil dispute resolution process in Indonesia. The focus of this research is to examine the manner in which judicial decisions provide legal clarity, fairness, and benefit to disputants. Using a normative juridical approach, the research explores relevant laws, legal precedents, and legal theories. The findings of the research show that judicial decisions play an important role in providing legal protection through three dimensions: first, as a source of legal certainty that binds all parties; second, as a representation of substantial justice to address the imbalance between parties; and third, as a dispute resolution tool that provides social benefits. The research also shows that the success of judges' decisions as a means of legal protection still faces various challenges, namely: inconsistencies in the application of precedents, variations in legal considerations, and problems in implementing decisions. The research recommends that there should be increased independence of the courts, standardisation in legal reasoning, and changes in the enforcement system to strengthen the role of judgments as a legal protection tool in civil disputes.